Implementasi Komunikasi Pemasaran Terpadu untuk Peningkatan Brand Awareness UMKM Draw Coffee - Santi Rimadias; Shalsa Bella Putri Irawan; Adinda Pambayun Indraswari; Shandy Surya Lazuardy; Maulana Fadhil; Seichant Mardhira (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in Indonesia's economy, but often find it difficult to adapt to the demands of marketing in the digital era. This community service aims to increase the marketing effectiveness of Draw Coffee MSMEs, a